The Advancement of ASMA: Highlights from the 2022 Annual Conference - Marshall Magnusen (Journal of Applied Sports Management, 2022)
The Applied Sport Management Association (ASMA) is a scholarly organization that aims to builds research partnerships between faculty and students as well as strong connections between scholars and students studying sport and practitioners working in the sport industry. Each year, ASMA hosts a national (international) conference. Since 2005, ASMA has progressed to become the preeminent outlet for students and faculty to present research in a collegial and professional environment as well as build strong connects with sport industry practitioners. As evidence of the continued growth of ASMA, several noticeable events took place at the 2022 annual conference. A brief summary is provided.
Keywords: ASMA; conference